2020
DOI: 10.1590/1678-4685-gmb-2019-0244
|View full text |Cite
|
Sign up to set email alerts
|

CRZ1 regulator and calcium cooperatively modulate holocellulases gene expression in Trichoderma reesei QM6a

Abstract: Trichoderma reesei is the main filamentous fungus used in industry to produce cellulases. Here we investigated the role of CRZ1 and Ca 2+ signaling in the fungus T. reesei QM6a concerning holocellulases production. For this, we first searched for potential CRZ1 binding sites in promoter regions of key genes coding holocellulases, as well as transcriptional regulators and sugar and calcium transporters. Using a nearly constructed T. reesei Dcrz1 strain, we demonstrated that most of the genes expected to be regu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 59 publications
1
10
0
1
Order By: Relevance
“…Furthermore, biomass breakdown is a complex process that involves several signaling pathways, not only those related to the regulation of genes encoding CAZymes. A detailed examination of the regulation of cellulolytic enzymes in T. reesei evidenced significant functions of the Ca 2+ sensing system and the regulator CRZ1 in the control of XYR1 and CRE1 [66]. These results support our findings that the transcripts predicted to be coexpressed with the studied TFs were not comprised only of transcripts encoding CAZymes, since other factors influence the complex regulation of hydrolytic enzyme genes.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, biomass breakdown is a complex process that involves several signaling pathways, not only those related to the regulation of genes encoding CAZymes. A detailed examination of the regulation of cellulolytic enzymes in T. reesei evidenced significant functions of the Ca 2+ sensing system and the regulator CRZ1 in the control of XYR1 and CRE1 [66]. These results support our findings that the transcripts predicted to be coexpressed with the studied TFs were not comprised only of transcripts encoding CAZymes, since other factors influence the complex regulation of hydrolytic enzyme genes.…”
Section: Discussionsupporting
confidence: 82%
“…Likewise, the interaction of the calcium binding proteins NCS (neuronal calcium sensor-like), phosphodiesterase, and ENVOY (a protein with PAS/LOV domain) have all been linked to the regulation of G protein signaling and its induction of cellulase gene expression [ 48 ]. Recently, Martins-Santana et al [ 49 ] showed that the deletion of CRZ1 (calcineurin-responsive zinc finger 1) affects the expression of cellulases in T. reesei and that Ca 2+ acts synergistically with CRZ1 to regulate gene expression in these fungi. However, Ca 2+ was also shown to exhibit a CRZ1 -independent regulatory role in T. reesei gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…, and Xyr1 (xylanase regulator 1), primarily in T. reesei are the prime transcriptional activators of the genes encoding cellulase ( cbh1, cbh2, egl1 , and bgl1 ) enzymes [ 98 ] RXE1 It (RXE1 orthologs in Aspergillus chrysogenum, Beauveria bassiana , and Fusarium oxysporum are designated BRLA) regulate cellulase gene expression, exhibits intense binding activity to the xyr1 promoter [ 99 ] Rce1 It acts as a transcriptional repressor for cellulase gene expression by binding at the cbh1 promoter region, antagonized Xyr1 from binding to the cbh1 promoter [ 100 ] BglR It positively regulates the expression of genes encoding BGL in T. reesei . Its activation causes repression of the CBH and EG genes [ 101 ] ClbR In A. aculeatus it regulates cellulase-encoding genes induced by cellulose and cellobiose [ 102 ] Ace3 In T. reesei , its overexpression led to increase cellulase gene expression, while its removal causes a remarkable reduction in cellulase activity [ 103 ] CreA/Cre1 They regulates CCR (carbon catabolite repression) where, in the existence of simple sugars such as glucose, fructose, mannose or xylose, it suppresses the transcription of genes encoding enzymes involved in the metabolism of more complex polysaccharides [ 104 ] Crz1 Through the conduction of Ca 2+ /Mn 2+ mediated signalling, it affects the promoter region of xyr1 and cbh1, and induced cellulase production [ 105 ], [ 135 ] Ctf1 In T. reesei , it downregulate RCE1 gene, thus it upregulate genes of the transcription factors XYR1 and ACE3, resulting in the activation of cellulolytic genes [ 106 ] Clr-1/Clr-2/Clr-3 Activation of the Clr-1 r...…”
Section: Molecular Mechanisms Behind the Cellulase Expressionmentioning
confidence: 99%